Vibrato and vowel identification - SUNDBERG, J. (Archives of Acoustics, 1977)
The influence of vibrato on vowel identification is studied in synthesized vowel sounds with fundamental frequencies between 300 and 1000 Hz. Phonetically trained subjects were asked to identify these stimuli presented with and without vibrato as any of 12 Swedish long vowels. Small and occasional effects are observed on the mean formant frequencies and the scatter of the responses. However, the effects are greater and more frequent than could be expected to occur by chance. In the majority of the cases, where the vibrato affected the responses, the vowel identification became somewhat harder when the stimulus was presented with vibrato. It is assumed that the vibrato may be used to conceal some of the deviations from the vowel qualities in speech which are typically made in singing.